2018
DOI: 10.1093/nar/gky631
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating uracil and 5-halouracils into short peptide nucleic acids for enhanced recognition of A–U pairs in dsRNAs

Abstract: Double-stranded RNA (dsRNA) structures form triplexes and RNA-protein complexes through binding to single-stranded RNA (ssRNA) regions and proteins, respectively, for diverse biological functions. Hence, targeting dsRNAs through major-groove triplex formation is a promising strategy for the development of chemical probes and potential therapeutics. Short (e.g., 6–10 mer) chemically-modified Peptide Nucleic Acids (PNAs) have been developed that bind to dsRNAs sequence specifically at physiological conditions. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 105 publications
2
60
0
Order By: Relevance
“…[ 102 ] Chen and coworkers studied the use of 5‐halouracils ( X U) in aminoethylglycine PNAs for targeting AU pairs in dsRNAs, and similarly found increased thermal stability for all halouracil‐thymine substitutions in PNA‐RNA triplexes, with the most pronounced stabilization observed for X = Br. [ 103 ] The 2‐thiouridine (s 2 U) base is a subtle O‐ > S modification of uridine, but has been shown to dramatically increase RNA duplex stability. The s 2 U sugar preferentially adopts a 3′‐endo pucker conformation due to increased steric interactions between the 2′‐hydroxyl and sulfur, which in turn favors A‐form RNA duplex formation via decreased conformational entropy.…”
Section: Unnatural Bases In Noncanonical Interactionsmentioning
confidence: 99%
“…[ 102 ] Chen and coworkers studied the use of 5‐halouracils ( X U) in aminoethylglycine PNAs for targeting AU pairs in dsRNAs, and similarly found increased thermal stability for all halouracil‐thymine substitutions in PNA‐RNA triplexes, with the most pronounced stabilization observed for X = Br. [ 103 ] The 2‐thiouridine (s 2 U) base is a subtle O‐ > S modification of uridine, but has been shown to dramatically increase RNA duplex stability. The s 2 U sugar preferentially adopts a 3′‐endo pucker conformation due to increased steric interactions between the 2′‐hydroxyl and sulfur, which in turn favors A‐form RNA duplex formation via decreased conformational entropy.…”
Section: Unnatural Bases In Noncanonical Interactionsmentioning
confidence: 99%
“…Nielsen and co‐workers showed that substituting the Hoogsteen‐binding T residues for substituted 1,8‐naphthyridin‐2(1 H )‐ones (Figure 2 a) in a PNA clamp led to increased binding of the PNA*DNA–PNA triplex [11] . Chen and co‐workers modified U bases [12] and showed that replacement of the thymine methyl with hydrogen or halogens might lower the p K a of the Hoogsteen‐binding pyrimidine, increasing binding affinity for A–U compared to T (Figure 2 b, X=H, F, Cl, Br, I; Y=O) [12a] . More recently, they reported that 2‐thiouracil (Figure 2 b, X=H; Y=S) enhances A–U binding in a position independent manner [12b] .…”
Section: Figurementioning
confidence: 99%
“…Expanding on our strategy of using extended PNA nucleobases for RNA recognition, [13] we envisioned a scaffold containing benzamide attached through an amide linkage to an isoorotic acid derived PNA ( Io , Figure 2 e). This design relied on presumed advantages including (1) attaching the pyrimidine base to an electron‐withdrawing group to increase the H‐bond donating ability of the uracil, [12a] (2) imparting enough rigidity across the extended π‐system to afford π‐stacking opportunities and entropic advantages for binding and, (3) planning a modular synthesis allowing modification of the extended nucleobase to achieve optimum planarity and binding.…”
Section: Figurementioning
confidence: 99%
“…Our data provide important insights into developing ligands targeting the tau pre-mRNA hairpin structure. For example, double-stranded RNAs (dsRNAs) may be targeted by chemically modified dsRNA-binding PNAs that show significantly reduced binding to single-stranded RNAs (ssRNAs) [72,74,75,76,77,78] and dsDNAs [72,74,75,76,77,78,79,80,81,82,83]. However, the application of dsRNA-binding PNAs for regulating tau pre-mRNA exon 10 splicing may not be ideal, because the splice site hairpin contains a relatively short dsRNA region (seven base pairs), and residues +5 to +7 (critical for U1 snRNP recognition) are not involved in stable base pairing interactions [21,29,84].…”
Section: Discussionmentioning
confidence: 99%